A MACHINE LEARNING APPROACH FOR PREDICTIVE ANALYSIS OF TRAFFIC FLOW - Bhartiya, Poonam; Bhatele, Mukta; Waoo, Akhilesh A (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Traffic congestion is a critical issue affecting urban areas globally, leading to significant economic and social costs. Predictive traffic flow analysis has emerged as a promising solution to mitigate congestion and enhance transportation efficiency. This paper proposes a machine learning approach for predictive analysis of traffic flow, leveraging the wealth of available data from various sources such as traffic sensors, GPS devices, and traffic cameras. This paper’s approach integrates historical traffic data with real-time information to forecast future traffic conditions accurately. employ a combination of machine learning techniques, including supervised and unsupervised learning algorithms, to model the complex dynamics of traffic flow. Feature engineering techniques are applied to extract meaningful features from raw data, facilitating the training of predictive models. Furthermore, it explores the use of advanced deep learning architectures, such as recurrent neural networks (RNNs) and convolutional neural networks (CNNs), for temporal and spatial analysis of traffic patterns. These models are trained on large-scale datasets to capture intricate relationships among different variables influencing traffic flow. Harnessing the power of machine learning can pave the way for smarter, more efficient transportation systems that enhance mobility and reduce congestion in urban environments.